DISTRIBUTION OF HEAVY METALS IN NATUNA COASTAL WATERS - Sophia L Sagala; Rikha Bramawanto; Anastasia R.T.D Kuswardani; Widodo S Pranowo (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACTThe study of Pb, Cd, Cu, Hg, and As and Fe in Natuna coastal waters, Riau Islands was conducted in November 2012. Water and sediment samples were collected from 35 stations by purposive sampling method and those heavy metals were analysed using Atomic Absorption Spectrophotometer, flame type (FAAS). The results showed that concentrations of total Pb, Cd, Cu, Hg, and As in surface water were below instrument detection limit (2 µg/L for Pb, Cd, and Cu; 0.02 µg/L for Hg and As). Moreover, the concentration of metal Fe in surface water was 0.021-0.054 mg/L. Concentrations of Pb and Cu in sediment were 0.05-22.67 mg/kg and 3.77-11.00 mg/kg, respectively, at which the highest concentrations were found near Binjai Estuary. Those concentrations were significantly below the standard levels set by CCME (2002) and ANZECC/ARMCANZ (2000). Concentration of Fe in sediment varied from 751.13-2309.12 mg/kg and showed similar spatial distribution to Cu-in-sediment. No standard level for Fe in waters was available. Generally, it can be concluded that Natuna coastal water was still uncontaminated. Keywords: heavy metals, iron metal, Natuna coastal waters.